Are ECG abnormalities common in black Africans with heart failure? Results from the Heart of Soweto study - Lee, Geraldine; Carrington, Melinda; Sliwa, Karen; Stewart, Simon (SA Heart Journal, 2017)
Background: The “Heart of Soweto” study is currently examining the pattern of cardiovascular disease (CVD) in Soweto, South Africa. Methods: As part of a large clinical registry of CVD patients presenting to the Chris Hani Baragwanath Hospital in Soweto, a 12-lead ECG was performed on 91% of “de novo” cases in 2006. Systematic analysis of the ECGs of heart failure patients was performed using detailed Minnesota coding. Results: A total of 756 de novo patients with HF (57% women, 88% Black African and mean age of 55 ± 16 years) had a 12-lead ECG. Overall, a major ECG abnormality was detected in 91% of cases consisting of ST segment changes, T wave changes, bundle branch blocks and arrhythmias. Minor abnormalities were noted in 97% of ECGs, such as axis deviation and high amplitude R waves. Left ventricular hypertrophy was evident in 15% (22% in those with a dilated cardiomyopathy) and a bundle branch block in 8% of ECGs (11% in those with an ischemic cardiomyopathy). Conclusion: Detailed examination of 12-lead ECGs of a large group of previously undiagnosed patients with HF in the Heart of Soweto study revealed many identifiable abnormalities. In addition to reconfirming the clinical utility of this cheap and practical diagnostic tool, these data highlight its potential role in screening for heart disease, particularly in low income communities.